Voices of Women Empowered by the INGO Field of Hope in Northern Uganda: A Phenomenological Study - Alexa M. Wilcox; M. Craig Edwards; Shida R. Henneberry; Joshua J. Ringer (Journal of International Agricultural and Extension Education, 2021)
Numerous studies support the role of improved agricultural practices in reducing poverty, and because much of the agricultural labor in lesser-developed countries (LDCs) is that of smallholder women farmers, many International Non-Governmental Organizations (INGOs) are implementing programs for these women. The United Nations prioritized gender equality and women’s empowerment in the Sustainable Development Goals (2015-2030) and encouraged governments and other actors, such as INGOs, to do the same. However, little qualitative research has been done to study the effectiveness of INGOs regarding women’s empowerment through improvements in their agricultural practices. This study was conducted to develop a deeper understanding of the lived experiences of womenin an INGO’s empowerment program. The study’s theoretical perspective conjoined critical and feminist theories. Twelve beneficiaries of the INGO Field of Hope’s projects in northern Uganda were interviewed. The responses were analyzed to develop four themes and 12 subthemes to understand their experiences and distill the phenomenon’s essence. We recommend that more research be done to assess which INGO practices encourage empowerment over dependency and whether such projects increase agricultural productivity
Keywords: livelihood improvement; phenomenology; women’s empowerment